The Role of Murabbi in Developing the Intelligence of Santri: A Comparative Study of Traditional and Modern Pesantren - Abdul Rosyad; Wawan Wahyudin; Endad Musaddad; Wasehuddin Wasehuddin (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Amid rapid socio-technological shifts, Islamic boarding schools (pesantren) face increasing demands to cultivate graduates who are intellectually competent, emotionally resilient, and spiritually grounded. Addressing this need, this study examines the role of the murabbi in developing santri intelligence through a comparative analysis of traditional and modern pesantren in Indonesia. Utilizing a qualitative comparative case study design, data were collected via in-depth interviews, participatory observation, and document analysis involving murabbi, institutional leaders, and santri. Findings reveal that the murabbi acts as a central pedagogical agent in fostering holistic intelligence across intellectual, emotional, and spiritual dimensions. In traditional pesantren, this role is profoundly relational, prioritizing spiritual mentoring and moral exemplarity to nurture emotional and spiritual growth. Conversely, modern pesantren employ structured curricula, academic assessments, and organized character-building programs to systematically integrate all three intelligences. Despite these methodological distinctions, both models share a foundational philosophy anchored in Islamic humanistic values. This research emphasizes the murabbi’s pedagogical agency as a critical determinant of holistic santri development. Practically, it provides strategic recommendations for pesantren leaders to enhance murabbi professional development, institutionalize compassionate mentoring practices, and align academic programs with spiritual-emotional formation, thereby strengthening value-based Islamic education in contemporary contexts.